1990
DOI: 10.1002/j.1460-2075.1990.tb08123.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ablation of a mouse gene expressed specifically in brain.

Abstract: The JB1075 gene was initially identified from a cDNA clone of a rat brain messenger RNA expressed in particular subsets of CNS neurons and pituitary cells. Although the protein encoded by this gene is of unknown function, its sequence suggests that it may be related to secretogranin proteins, which are found in association with secretory granules in a variety of peptidergic endocrine and neuronal cells. Here we show that the mouse 1B1075 gene is located between the dilute (d) and short ear (se) genes on chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…SgIII mRNA is expressed in particular subsets of central nervous system neurons (36), pituitary cells (32), and various endocrine cells (8). Mice missing the SgIII gene revealed no major obvious effects on viability, fertility, or locomotor behavior, so that SgIII is not required for their survival (37). However, because SgIII is a residential protein in SGs, Martens and colleagues (38) have addressed its secretory function using the Xenopus pituitary intermediate lobe.…”
Section: Discussionmentioning
confidence: 99%
“…SgIII mRNA is expressed in particular subsets of central nervous system neurons (36), pituitary cells (32), and various endocrine cells (8). Mice missing the SgIII gene revealed no major obvious effects on viability, fertility, or locomotor behavior, so that SgIII is not required for their survival (37). However, because SgIII is a residential protein in SGs, Martens and colleagues (38) have addressed its secretory function using the Xenopus pituitary intermediate lobe.…”
Section: Discussionmentioning
confidence: 99%
“…because mice missing the 1b1075 gene exhibited no apparent defects in viability, fertility, or locomotor behavior [83], functional analyses of sgiii were relatively overlooked in 1990s. only Martens and colleagues reported that the mrna levels of both PoMC, a precursor of Msh, and sgiii in the Xenopus pituitary intermediate lobe were coordinately elevated when Xenopus was placed on a black background from a white background, suggesting the involvement of sgiii in the regulation of secretory processes [84].…”
Section: Sgiii: a Bridge Between The Core Aggregate And Cholesterol-rmentioning
confidence: 99%
“…Currently, Cga is thought to be a unique binding partner for sgiii within the aggregate. however, other soluble binding cargo proteins that specifically bind to sgiii may be identified in the future, because sgiii is more ubiquitously expressed in the neuroendocrine cells than Cga [80][81][82][83]. in addition to the mechanism mediated by sgiii, similar mechanisms connecting aggregates of soluble cargo molecules with the sorting/processing platform on the membrane likely exist.…”
Section: Stepmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that alternative metabolic pathways are activated in transgenic tobacco plants deficient in cytosolic pyruvate kinase (30) and in null mutants of the mouse affecting glycerol-3-phosphate dehydrogenase (31) and brain-specific proteins (32). Functional redundancy has also been proposed to account for the lack of phenotypic effects in antisense transformants affecting the En-i and En-2 homeobox genes of Drosophila (33) and the Q genes of the mouse major histocompatability complex (34).…”
mentioning
confidence: 99%